IMAMAH DALAM PERSPEKTIF KEMASLAHATAN RAKYAT - Wahyu Abdul Jabar (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2017)
Abstract: This study will describe in detail the concept of Imamate (leadership) in the perspective of the people’s welfare. Imamah in a government can be said to represent the interests of its people if the government based on the principles musyawaroh, musyawamah, huriyyah and al-adalah. These principles are important in the government to ensure that policies are made will be able to realize the benefit of the people, not the benefit of a few people. However, these principles will be difficult to be realized if the helm of the government was not an expert. Therefore the scholars make standardization for people who want to become a leader, among others: Islamic, independent, puberty, male, intelligent, adult, is, Has knowledge and experience, Have a strong personality, brave, and not easily give up. In performing its duties, a leader will be accompanied by ahlul halli wal aqdi. They will assist in formulating and establishing a policy in which government is based on the principle of consultation so that people benefit will be realized.Keywords: Imamate, welfare, people